Vitamin D deficiency may affect the glucose uptake in l6 cells by affecting themitochondrial metabolism - SAMIKSHA KUKAL,; NANCY TANEJA,; SHALINI MANI, (International Journal of Pharma and Bio Sciences, 2016)
The present study is an attempt to understand the role of vitamin D deficiency in pathogenesis of diabetes and put forth a possible explanation for its mechanism of action. Skeletal muscle cells (L6) were separately grown in media with very low vitamin D as well as optimized dose (10-9M) of vitamin D supplemented media. It was observed that L6 cells grown in presence of vitamin D (10-9M) exhibited high glucose and high calcium uptake as compared to the cells grown in low concentration of vitamin D. As mitochondrial defects are another crucial factor to cause the diabetes and vitamin D is known to improve the mitochondrial metabolism. Hence, in order to study the same, we also determined the activity of NADH oxidase and catalase in all set of experiments. In correlation with calcium and glucose uptake assays, the activity of these enzymes was also found to be improved in presence of vitamin D supplementation. Hence putting all the observations together, the anti-diabetic function of vitamin D can be possibly due to improvement in mitochondrial metabolism.